Industrialisasi dan Kesejahteraan Sosial di Mangkunegaran Awal Abad ke-20 - Muhammad Misbahuddin (CV Edujavare Publishing, 2025)
This article explores and explains the industrialization process that occurred in one of the Vorstenlanden areas, namely Swapraja Mangkunegaran. The industrialization process had a significant impact on the increase in social violence and changes in the landscape of public health understanding in Mangkunegaran. This historical research uses a sociological approach using Michel Foucault's theory of power discourse as its unit of analysis. This article argues that industrialization has significantly impacted efforts to rationalize public health. The process of health rationalization is often seen as having no direct relationship with industrialization. However, this article finds the opposite data, where industrialization goes hand in hand with increasing the rationality of public health awareness.